Dampak Program Dana Bergulir Bagi Usaha Kecil dan Menengah (UKM) - Setiawan, Achma Hendra; Rejekiningsih, Tri Wahyu (Jurnal Ilmu Ekonomi ASET, 2009)
The financial program to public sector was revolving fund by Department ofCooperation and Small and Medium Enterprises can be improving incomeâs public sectorsand small and medium enterprises. Fragment, with revolving fund, small and medium enterprisescan absorb labor force. So, revolving fund must be continuing for small and medium enterprises.By revolving fund, small and medium enterprises have to increase on employee (75%), capital(35.71%), economic scale (50%) and profit (50.27%). Coefficient of correlation 0.8819 ismeans that small and medium enterprises can be absorb of labor force. So, the revolving fundfor small and medium enterprises was continuing and more than before. Fragment, to purposeemployment and growing up of economy.Keywords : revolving fund, small and medium enterprises.